Serum-Based Protein Biomarkers in Blast-Induced Traumatic Brain Injury Spectrum Disorder - Elsayed, Mohammad; Agoston, Denes V. (Frontiers in Neurology, 2012)
The biological consequences of exposure to explosive blast are extremely complex. Serum protein biomarkers in blast-induced TBI (bTBI) can aid in determining injury severity, monitoring progress, and predicting outcome. Exposure to blast results in varying degrees of physical injury. Explosive blast can also induce psychological stress that can contribute to or amplify the extent of physical damage. Given the complexity, the scale of injury, and variety of symptoms, bTBI may be best described as a spectrum disorder. In this focused review, we summarize the status of serum protein biomarkers in bTBI in the context of the classification and pathological changes of other forms of TBI. Finally, we recommend specific and easily implementable measures to accelerate serum protein biomarker discovery and validation in bTBI.